Patient-reported outcomes in head and neck and thyroid cancer randomised controlled trials: A systematic review of completeness of reporting and impact on interpretation. (March 2016) - Mercieca-Bebber, Rebecca L.; Perreca, Alessandro; King, Madeleine; Macann, Andrew; Whale, Katie; Soldati, Salvatore; Jacobs, Marc; Efficace, Fabio
Abstract: Aim: To determine the completeness of reporting of patient-reported outcomes (PROs) of head and neck cancer (HNC) and thyroid cancer randomised-controlled trials (RCTs) and identify PRO measures used. Methods: A systematic literature search was conducted for HNC and thyroid cancer RCTs with PRO end-points (January 2004–June 2015). Two investigators independently extracted data, assessed adherence to the International Society for Quality of Life Research (ISOQOL) PRO reporting standards and concordance between hypotheses and PRO measures used. Data were entered into the Patient-Reported Outcomes Measurements Over Time in Oncology (PROMOTION) Registry. Results: Sixty-six RCTs were included, 56 (85%) HNC and 10 (15%) thyroid cancer. Twenty-two (33%) included a primary and 44 (67%) included a secondary PRO end-point. A total of 40 unique PRO measures were used. Adherence to the ISOQOL PRO reporting standards was higher for RCTs with primary PRO end-points than for secondary PRO end-points: (mean adherence of 43% and 29% respectively). Completeness of PRO reporting did not improve with time: r = .13, p = .31. ISOQOL checklist items poorly reported included: PRO hypothesis (reported for eight RCTs, 12%), justification chosen of PRO measures (n = 16, 24%), rates of missing PRO data (n = 19, 29%), and generalisability of results (n = 12, 18%). Encouragingly, PROs were identified in 55 RCT abstracts (83%) and PRO results interpreted for 30 RCTs (45%). Conclusions: Reporting of PRO end-points was more comprehensive in RCTs with primary rather than secondary PRO end-points. Improvement is needed in the transparent reporting of PRO studies, particularly regarding data collection, analyses and generalisability of PRO results. Highlights: Key PRO aspects of head and neck (HNC) and thyroid cancer trials were often unreported. Incomplete reporting of PROs is potentially a barrier to interpretation & translation. There was no significant improvement in PRO reporting over time in this cohort. 40 unique PRO measures were used across the 66 HNC and thyroid cancer RCTs. Eight RCTs reported a PRO hypothesis; all of which chose a well-suited PRO measure.